2019
DOI: 10.1016/j.aap.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Implications of estimating road traffic serious injuries from hospital data

Abstract: To determine accurately the number of serious injuries at EU level and to compare serious injury rates between different countries it is essential to use a common definition. In January 2013, the High Level Group on Road Safety established the definition of serious injuries as patients with an injury level of MAIS3+(Maximum Abbreviated Injury Scale). Whatever the method used for estimating the number or serious injuries, at some point it is always necessary to use hospital records. The aim of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Similar results to our study have also been presented earlier by Pérez et al [6] who compared the number of MAIS 3+ patients between the ICD-AIS map by AAAM and direct AIS coding. They used a German data set (n = 209) and concluded that the ICD-AIS map underestimated the amount of seriously injured patients by 20% [6], which is nearly the same figure as ours. However, they used a German version of ICD-10 (ICD-10-GM) which is, to some extent, more specific than the ICD-10 used in Finland.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
See 4 more Smart Citations
“…Similar results to our study have also been presented earlier by Pérez et al [6] who compared the number of MAIS 3+ patients between the ICD-AIS map by AAAM and direct AIS coding. They used a German data set (n = 209) and concluded that the ICD-AIS map underestimated the amount of seriously injured patients by 20% [6], which is nearly the same figure as ours. However, they used a German version of ICD-10 (ICD-10-GM) which is, to some extent, more specific than the ICD-10 used in Finland.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…However, they used a German version of ICD-10 (ICD-10-GM) which is, to some extent, more specific than the ICD-10 used in Finland. In general, several studies indicate that different kinds of automatic ICD-AIS conversion tools generates rather lower than higher numbers of serious injuries than direct AIS coding [6,[14][15][16]. The reliability of input data, and more specifically, the quality and accuracy of ICD injury coding, is essential for the successful conversion and has a significant impact on the results.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations